Co-production of low technical readiness level climate science through prototyping with users. Prospects in a European case study - E. Delpiazzo; K. Bülow; E. Baulenas Serra; C. Teichmann; J.H. Christensen; D. Matte; D. Bojovic; P. Kalverla; B.B. B. Booth; C.R. Goddard; F. Fung; B. Solaraju-Murali; et al. (Environmental Science & Policy, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Range‐extending fish become competitive dominants under ocean warming but not heatwaves or acidification - Angus Mitchell; Ericka O. C. Coni; Sean D. Connell; David J. Booth; Ben P. Harvey; Sylvain Agostini; Timothy Ravasi; Ivan Nagelkerken (Ecology, 2026)
Ocean warming is driving species range extensions into cooler regions. The direct physiological influence of warming on species performance can accelerate such extensions into novel ecosystems; however, indirect effects of invader–resident interactions in cooler regions may counter these positive effects. Here, we examined the foraging performance and densities of competing warm‐water and cool‐water fishes across a latitudinal temperature gradient spanning 1500 km from tropical to temperate reefs subjected to rapid ocean warming in the southern hemisphere, and across natural analogs of temperate, tropicalized, and acidified reef localities in the northern hemisphere, and during a severe marine heatwave at a temperate reef. While current levels of ocean warming have allowed the warm‐water fish to extend their ranges into temperate ecosystems at both hemispheres, their foraging performance was reduced at both the cold‐ and warm‐temperate reefs compared to the (sub)tropical reefs. However, at the (warmer) tropicalized reef, the warm‐water fish had higher foraging performance and maintained densities, even under extreme pH reduction, compared to the temperate reef. In contrast, the cool‐water species struggled at the warmer tropicalized and extreme reefs with reduced foraging performance and lower population densities compared to the temperate reef. Contrastingly, the severe heatwave experienced at the temperate reef did not alter the foraging behaviors of either species. We suggest that ocean warming boosts the foraging performance of the range‐extending warm‐water fish and impairs that of their cool‐water competitor at temperate reefs, irrespective of acidification and heatwaves, leading to a shift in dominance hierarchies on temperate reefs. We conclude that warming‐driven increases in foraging performance of the warm‐water species may alleviate foraging limitations and enhance its establishment at its leading range edges under climate change, to the detriment of its cool‐water competitors.

Skeletal muscle atrophy induced by aging and disuse atrophy are strongly associated with the upregulation of the endoplasmic stress protein CHOP in rats - J. Max Michel; Joshua S. Godwin; Nathan R. Kerr; Thomas E. Childs; Frank W. Booth; C. Brooks Mobley; David C. Hughes; Michael D. Roberts (Molecular Biology Reports, 2025)
Background While canonical anabolic and proteolytic pathways have been well examined in the context of skeletal muscle proteostasis, the roles of endoplasmic reticulum stress (ERS) and the induced unfolded protein response (UPR) are underappreciated. Thus, we aimed to determine whether aging and/or disuse atrophy in rats altered skeletal muscle ERS/UPR markers. Methods and Results Soleus (SOL) and plantaris (PLT) muscles of 3-month-old (mo), 6 mo, 12 mo, 18 mo, and 24 mo rats (9–10 per group, 48 in total) were analyzed for UPR proteins with further analysis performed on the protein CHOP. The gastrocnemius muscles of 4 mo rats that had undergone hindlimb immobilization (HLI, n = 12) or sham casting (CTL, n = 12) were analyzed for similar targets as well as more extensive CHOP-related targets. CHOP protein was greater in the PLT and SOL of 18 and 24 mo rats versus other age groups ( P < 0.05). Moreover, negative correlations existed between CHOP expression and normalized PLT ( R =-0.702, P < 0.001) and SOL ( R =-0.658, P < 0.001) muscle weights in all rats analyzed at different ages. CHOP protein expression was also greater in the gastrocnemius of HLI versus CTL rats ( P < 0.001), and a negative correlation existed between CHOP protein expression and normalized muscle weights in these rats ( R =-0.814, P < 0.001). Nuclear CHOP protein levels ( P < 0.010) and genes transcriptionally regulated by CHOP were also greater in HLI versus CTL rats ( P < 0.001) implicating transcriptional activity of CHOP is elevated during disuse atrophy. Conclusions CHOP is operative during aging- and disuse-induced skeletal muscle atrophy in rodents, and more research is needed to determine if CHOP is a key mechanistic driver of these processes.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Eliciting the magnitude of auditory threshold shift considered injury in Antarctic marine mammals - U.K. Verfuss; A.K. Darias-O’Hara; C. Erbe; D. Houser; V.M. Janik; D. Ketten; K. Lucke; M. Morell; A. Pacini; C. Reichmuth; C.G. Booth (Marine Policy, 2024)

Ecological and archaeological consequences of ongoing, largely human‐mediated colonisation of endemic soft, shelly habitats by mangroves in a northern New Zealand embayment - John D. Booth; James J. Robinson; Reuben C. Booth; Robert S. Willoughby (New Zealand Journal of Marine and Freshwater Research, 2024)
Areal extent of native mangroves, Avicennia marina , has doubled in Bay of Islands since 1951. This expansion is widely attributed to deforestation and poor land‐use practices beginning in the late 1800s to early 1900s, and led to greatly transformed intertidal and supratidal habitats. One example has been the ecological isolation and crowding (sometimes, colonisation) by mangroves of shelly beaches, together with their associated ‘chenier‐like’ spits – themselves now among the rarest of New Zealand's inshore marine habitats, with only six still relatively intact ecologically out of at least 44 in the Bay of Islands. These shores were also where pre Contact Māori often gathered to harvest intertidal cockles Austrovenus stutchburyi and to fish, archaeological signatures typically becoming obscured once mangroves colonised upper shores. Although recent seaward intrusion by mangroves into the cockle habitat of the Parekura Bay study site appears to have been proportionately small, there may be potential for more as elevated levels of sedimentation persist. With wholesale mangrove removals demonstrably ineffective in re‐establishing original communities, the ongoing ecological and archaeological disruption of endemic soft, shelly contexts through largely human‐mediated mangrove colonisation might be curbed in certain situations through strategic, proactive removal of new mangrove recruits, particularly on expanding edges.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Subglacial bedform and moat initiation beneath Rutford Ice Stream, West Antarctica - Rebecca Schlegel; Alex M. Brisbourne; Andrew M. Smith; Adam D. Booth; Tavi Murray; Edward C. King; Roger A. Clark (Geomorphology, 2024)

Further insights into killer whales Orcinus orca preying on white sharks Carcharodon carcharias in South Africa - A Towner; P Micarelli; D Hurwitz; MJ Smale; AJ Booth; C Stopforth; E Jacobs; FR Reinero; V Ricci; A Di Bari; S Gavazzi; G Carugno; et al. (African Journal of Marine Science, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Futures for invasive alien species management: using bottom-up innovations to envision positive systemic change - J. L. van Velden; R. Biggs; T. Hichert; P. Booth; C. Büchner-Marais; K. J. Esler; M. Lewarne; L. J. Potgieter; S. J. Rahlao; A. J. Rebelo; T. B. Robinson; N. J. van Wilgen; et al. (Sustainability Science, 2023)
Invasive alien species (IAS) pose a key threat to biodiversity, the economy and human well-being, and continue to increase in abundance and impact worldwide. Legislation and policy currently dominate the global agenda for IAS, although translation to localised success may be limited. This calls for a wider range of responses to transform IAS management. An under-appreciated strategy to achieve success may come from bottom-up, experimental innovations (so-called “seeds”), which offer alternative visions of what may be possible for IAS management in the future. We present an application of a participatory process that builds on such innovations to create alternative visions of the future, with actionable pathways to guide change. Through a series of workshops with practitioners and academics, we used this process to explore alternative positive futures for IAS management in South Africa. We then identified a set of domains of change, that could enable these visions to be actioned by appropriate stakeholders. The domains of change highlight the social–ecological nature of the IAS sector, with interconnected actions needed in financial, cultural, social, technological and governance spheres. Key domains identified were the need to shift mindsets and values of society regarding IAS, as well as the need for appropriate and functional financing. This participatory futuring process offers a way to interrogate and scale bottom-up innovations, thereby creating optimism and allowing stakeholders to engage constructively with the future. This represents an important step in fostering the potential of bottom-up innovations to transform IAS management.

Grazing Increases Soil Warming in Headwater Wetlands: Importance to Land Managers and Water Users - D. Terrance Booth; John C. Likins; Samuel E. Cox; Jay B. Norton; Richard C. Anderson-Sprecher (Ecosystems, 2022)
The earth’s mountains continue to lose water. Glaciers are melting and mountain snow/rain balance tilts increasingly liquescent. Water is running off sooner—sometimes overfilling reservoirs, causing flooding, and setting the stage for late-season shortages. One adaptive strategy is to recover and enhance water-storage capacities of headwater riparian systems. Grazing, a common use of headwater lands, affects both soils and vegetation. To better understand how grazing might affect water storage and other ecosystem services of high elevation riparian wetlands, we measured soil-profile temperatures, soil organic matter (SOM), and phytomass at six sites in the upper Sweetwater River sub-basin of Wyoming, USA, where fence lines allowed us to contrast grazing management. We found grazed wetlands consistently had warmer soils than fenced wetlands. We found added evidence that SOM is important in both soil temperature control and water-storage potential of wetlands. We review evidence that warmer soil temperatures and drying cause loss of SOM with the implied concomitant C losses through erosion and emissions. We recommend land managers of temperate-climate headwater systems consider the need to end growing seasons with full stands of riparian vegetation to reduce soil warming and to build organic matter—particularly on lands where municipalities and other downstream water users are seeking long-term increases in water yields and less flooding.

Plesiochorus irwinorum n. sp. (Trematoda: Gorgoderidae) from the urinary bladder of the hawksbill turtle, Eretmochelys imbricata (Testudines: Cheloniidae), off the east coast of Australia - Richard D. Corner; Rosemary J. Booth; Scott C. Cutmore (Systematic Parasitology, 2022)
Plesiochorus Looss, 1901 is a genus of Gorgoderidae infecting the urinary bladders of marine turtles globally. Currently, just two morphologically similar species are recognised, Plesiochorus cymbiformis (Rudolphi, 1819) Looss, 1901 and Plesiochorus elongatus Pigulevsky, 1953, which have been distinguished by molecular data and subtle morphological differences. Here we describe a new species, Plesiochorus irwinorum n. sp. , infecting hawksbill turtles ( Eretmochelys imbricata (L.)), which is primarily distinguished from the other two species of Plesiochorus on the basis of ITS2, cox 1 and 28S sequence data. Morphometric data for specimens examined during this study overlap between P . cymbiformis and P . irwinorum n. sp. for every measured feature, rendering them functionally cryptic. However, principal components analysis clearly distinguishes the two species. Additionally, we report new specimens of P . cymbiformis , and provide new sequence data for specimens from Australian loggerhead ( Caretta caretta (L.)) and hawksbill turtles. There is little understanding of the host-specificity or geographical distribution of the three species of Plesiochorus , and it remains possible that some of the previously reported sequences have been attributed to the wrong species.

Modeling population effects of the Deepwater Horizon oil spill on a long‐lived species - Lori H. Schwacke; Tiago A. Marques; Len Thomas; Cormac G. Booth; Brian C. Balmer; Ashley Barratclough; Kathleen Colegrove; Sylvain De Guise; Lance P. Garrison; Forrest M. Gomez; Jeanine S. Morey; Keith D. Mullin; et al. (Conservation Biology, 2022)
The 2010 Deepwater Horizon (DWH) oil spill exposed common bottlenose dolphins ( Tursiops truncatus ) in Barataria Bay, Louisiana to heavy oiling that caused increased mortality and chronic disease and impaired reproduction in surviving dolphins. We conducted photographic surveys and veterinary assessments in the decade following the spill. We assigned a prognostic score (good, fair, guarded, poor, or grave) for each dolphin to provide a single integrated indicator of overall health, and we examined temporal trends in prognostic scores. We used expert elicitation to quantify the implications of trends for the proportion of the dolphins that would recover within their lifetime. We integrated expert elicitation, along with other new information, in a population dynamics model to predict the effects of observed health trends on demography. We compared the resulting population trajectory with that predicted under baseline (no spill) conditions. Disease conditions persisted and have recently worsened in dolphins that were presumably exposed to DWH oil: 78% of those assessed in 2018 had a guarded, poor, or grave prognosis. Dolphins born after the spill were in better health. We estimated that the population declined by 45% (95% CI 14–74) relative to baseline and will take 35 years (95% CI 18–67) to recover to 95% of baseline numbers. The sum of annual differences between baseline and injured population sizes (i.e., the lost cetacean years) was 30,993 (95% CI 6607–94,148). The population is currently at a minimum point in its recovery trajectory and is vulnerable to emerging threats, including planned ecosystem restoration efforts that are likely to be detrimental to the dolphins’ survival. Our modeling framework demonstrates an approach for integrating different sources and types of data, highlights the utility of expert elicitation for indeterminable input parameters, and emphasizes the importance of considering and monitoring long‐term health of long‐lived species subject to environmental disasters. Article impact statement : Oil spills can have long‐term consequences for the health of long‐lived species; thus, effective restoration and monitoring are needed.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Phenotypic responses in fish behaviour narrow as climate ramps up - Almendra Rodriguez-Dominguez; Sean D. Connell; Ericka O. C. Coni; Minami Sasaki; David J. Booth; Ivan Nagelkerken (Climatic Change, 2022)
Natural selection alters the distribution of phenotypes as animals adjust their behaviour and physiology to environmental change. We have little understanding of the magnitude and direction of environmental filtering of phenotypes, and therefore how species might adapt to future climate, as trait selection under future conditions is challenging to study. Here, we test whether climate stressors drive shifts in the frequency distribution of behavioural and physiological phenotypic traits (17 fish species) at natural analogues of climate change (CO 2 vents and warming hotspots) and controlled laboratory analogues (mesocosms and aquaria). We discovered that fish from natural populations (4 out of 6 species) narrowed their phenotypic distribution towards behaviourally bolder individuals as oceans acidify, representing loss of shyer phenotypes. In contrast, ocean warming drove both a loss (2/11 species) and gain (2/11 species) of bolder phenotypes in natural and laboratory conditions. The phenotypic variance within populations was reduced at CO 2 vents and warming hotspots compared to control conditions, but this pattern was absent from laboratory systems. Fishes that experienced bolder behaviour generally showed increased densities in the wild. Yet, phenotypic alterations did not affect body condition, as all 17 species generally maintained their physiological homeostasis (measured across 5 different traits). Boldness is a highly heritable trait that is related to both loss (increased mortality risk) and gain (increased growth, reproduction) of fitness. Hence, climate conditions that mediate the relative occurrence of shy and bold phenotypes may reshape the strength of species interactions and consequently alter fish population and community dynamics in a future ocean.

The Influence of Legacy P on Lake Water Quality in a Midwestern Agricultural Watershed - Melissa Motew; Xi Chen; Eric G. Booth; Stephen R. Carpenter; Pavel Pinkas; Samuel C. Zipper; Steven P. Loheide; Simon D. Donner; Kai Tsuruta; Peter A. Vadas; Christopher J. Kucharik (Ecosystems, 2017)

Response to “Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al” - Alexandra C. G. Thomson; Paul H. York; Tim M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2016)

Headcut Erosion in Wyoming’s Sweetwater Subbasin - Samuel E. Cox; D. Terrance Booth; John C. Likins (Environmental Management, 2016)

Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism - Alexandra C. G. Thomson; Paul H. York; Timothy M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2015)

Fenceline contrasts: grazing increases wetland surface roughness - D. T. Booth; S. E. Cox; J. C. Likins (Wetlands Ecology and Management, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Population genetic structure and colony breeding system in dampwood termites (Zootermopsis angusticollis and Z. nevadensis nuttingi) - W. Booth; C. S. Brent; D. V. Calleri; R. B. Rosengaus; J. F. A. Traniello; E. L. Vargo (Insectes Sociaux, 2012)

Malaria severity and human nitric oxide synthase type 2 (NOS2) promoter haplotypes - Marc C. Levesque; Maurine R. Hobbs; Charles W. O’Loughlin; Jennifer A. Chancellor; Youwei Chen; Ariana N. Tkachuk; Jennifer Booth; Kistie B. Patch; Sallie Allgood; Ann R. Pole; Carolyn A. Fernandez; Esther D. Mwaikambo; et al. (Human Genetics, 2010)

Hydroelectricity and fish: a synopsis of comprehensive studies of upstream and downstream passage of anadromous wild Atlantic salmon, Salmo salar, on the Exploits River, Canada - D. A. Scruton; C. J. Pennell; C. E. Bourgeois; R. F. Goosney; L. King; R. K. Booth; W. Eddy; T. R. Porter; L. M. N. Ollerhead; K. D. Clarke (Hydrobiologia, 2008)

Conventional and EMG telemetry studies of upstream migration and tailrace attraction of adult Atlantic salmon at a hydroelectric installation on the Exploits River, Newfoundland, Canada - D. A. Scruton; R. K. Booth; C. J. Pennell; F. Cubitt; R. S. McKinley; K. D. Clarke (Hydrobiologia, 2007)

Bio‐optical consequences of viral infection of phytoplankton: I. Experiments with the cyanobacterium, Synechococcus sp. - W. M. Balch; J. M. Vaughn; J. I. Goes; J. F. Novotny; D. T. Drapeau; E. S. Booth; C. L. Vining (Limnology and Oceanography, 2007)
Four strains of the cyanobacteria, Synechococcus , were infected with viruses isolated and purified from coastal waters of the Gulf of Maine. Changes in host and virus concentration were observed in time course experiments, along with associated variability in inherent optical properties. There were strong optical shifts before and after lysis in inherent optical properties on time scales commensurate with the viral infection process. Specifically, both backscattering and absorption (particularly in visible wavelengths) increased slightly after infection, but decreased markedly after lysis. The most rapid optical change was seen in in vivo chlorophyll fluorescence, with a slight increase within 2 d after initial infection. Such changes likely reflect fundamental changes in host photophysiology after infection. After host lysis, there was a major drop in bulk Chl a fluorescence, synchronous with a major increase in the ratio of free viruses per host cell. The net effect of the changes in fluorescence and host concentration was an increase in the fluorescence per cell. These optical changes were accompanied by major changes in the submicron particle size spectra as cells were lysed, releasing their intracellular contents.

Variability in growth of longfinned eels among coastal catchments of south‐eastern Australia - C. T. Walsh; B. C. Pease; S. D. Hoyle; D. J. Booth (Journal of Fish Biology, 2006)
Longfinned eels Anguilla reinhardtii were captured by both fishery‐dependent and independent sampling methods from three rivers in New South Wales, south‐eastern Australia. Growth rates were examined in two zones (fresh water and tidal) in the Hacking, Hawkesbury and Clarence Rivers. Mean annual growth increments of sampled longfinned eels ranged from 30 to 60 mm year −1 using age‐length analyses and up to 167 mm year −1 based on tag‐recapture model estimates (GROTAG), with both methods showing high intra‐ and inter‐population variability. Growth was significantly faster in younger (5–15 years) fish than older (>15 years) fish, with females growing an average 10 mm year −1 faster than males of similar age and capture location. Longfinned eels found in tidal areas grew significantly faster than those in non‐tidal freshwater areas as a result of longer growing seasons in the highly productive estuarine habitats. Other possible factors influencing variability in growth rates for this species include habitat preference, density and fishing pressure.

Gene expression and genotyping studies implicate the interleukin 7 receptor in the pathogenesis of primary progressive multiple sclerosis - D. R. Booth; A. T. Arthur; S. M. Teutsch; C. Bye; J. Rubio; P. J. Armati; J. D. Pollard; R. N. S. Heard; G. J. Stewart (Journal of Molecular Medicine, 2005)

Variation in the sex ratio, size and age of longfinned eels within and among coastal catchments of south‐eastern Australia - C. T. Walsh; B. C. Pease; D. J. Booth (Journal of Fish Biology, 2004)
Longfinned eels Anguilla reinhardtii were captured by both fishery‐dependent and independent sampling methods from three rivers in New South Wales, south‐eastern Australia. Sex ratios, catch per unit effort and population age and total length structure were examined in three zones (fresh water and upper and lower tidal) in the Hacking, Hawkesbury and Clarence Rivers. Females were found in relatively high proportions in all zones, ranging from 97% in a freshwater (non‐tidal) site down to 59% in a tidal site. Males were found primarily in tidal zones (only two of the 677 longfinned eels caught in non‐tidal fresh water were males), with the greatest proportions being found in the brackish upper tidal areas. The mean number of fish captured per trap was higher in the fresh water and upper tidal zones than in the lower tidal zones. The mean ± s . e . age, 17·9 ± 0·3 years, and age range, 5–52 years for females were significantly higher than those of males 12·2 ± 0·4 years; range 5–22 years, which is typical of other anguillid species. Longfinned eels captured in fresh water were found be significantly larger and older than those in tidal zones due to the almost exclusive predominance of females.

Sexual dimorphism and gonadal development of the Australian longfinned river eel - C. T. Walsh; B. C. Pease; D. J. Booth (Journal of Fish Biology, 2003)
The sex and stage of gonadal development of longfinned river eels Anguilla reinhardtii , captured from nine river catchments in New South Wales, Australia, between 1999 and 2001, were determined macroscopically. Sex was verified by histology. Histology was also necessary, however, to accurately define stages of gonadal development, particularly in individuals Anguilla reinhardtii displayed asynchronous gamete development. The most advanced cells present in migrating male and female A. reinhardtii were spermatocytes and pre‐vitellogenic oocytes, respectively. Gonadal development stages were positively correlated with body size in both sexes. Females, however, were significantly larger than males and their gonads matured over a broader size range. Size at sexual differentiation (42–60 cm for males and 50–76 cm for females) was much larger than for most other anguillids that have been studied, with the exception of the New Zealand longfinned eel Anguilla dieffenbachii . Corresponding with its large range in size at sexual differentiation was a relatively large range in size at migration for both males (44–62 cm) and females (74–142 cm).

A novel artificial habitat collection device for studying resettlement patterns in anguillid glass eels - V. Silberschneider; B. C. Pease; D. J. Booth (Journal of Fish Biology, 2001)
The number of glass eels Anguilla australis and A. reinhardtii caught in artificial habitat collectors, made from a PVC base and polyethylene split rope fibres, was related to the number of rope fibre tufts attached to each collector rather than collector area directly. Ageing of collectors in situ to promote algal growth enhanced the catch of glass eels. Glass eels entered the collectors at night primarily during the flood tide, and did not move into the collectors during daylight hours. Glass eel abundance increased with increasing distance from the freshwater drain located in the causeway. The artificial habitat collectors are effective for assessing relative numbers of resettling glass eels and may be useful for studying recruitment and settlement patterns of other anguillid eel species, as well as identifying areas and habitats within a catchment that provide important shelter for glass eels. Sampling glass eels can be carried out with maximum effect and minimum effort using compact, aged artificial habitat collectors on the night time flood tide when low tide coincides with dusk.

Development of a carcinogenic potency index for dermal exposure to viscous oil products - Henk C. A. Brandt; Ewan D. Booth; Paul C. de Groot; William P. Watson (Archives of Toxicology, 1999)

Studies on the dermal and systemic bioavailability of polycyclic aromatic compounds in high viscosity oil products - David Potter; Ewan D. Booth; Henk C. A. Brandt; Robert W. Loose; Robert A. J. Priston; Alan S. Wright; William P. Watson (Archives of Toxicology, 1999)

Correlation of 32 P-postlabelling-detection of DNA adducts in mouse skin in vivo with the polycyclic aromatic compound content and mutagenicity in Salmonella typhimurium of a range of oil products - Ewan D. Booth; Henk C. A. Brandt; Robert W. Loose; William P. Watson (Archives of Toxicology, 1998)